Exploring the Impact of Social-Emotional Learning (SEL) on Cognitive and Emotional Development in Adolescents: A Review of Evidence from Educational Settings - Benjamin Cheunge; Kalina Christoeff Hadjiilieva; Anieta DeLongis; James Ennse (Journal of Teaching and Learning, 2026)
This study aims to explore the impact of Social-Emotional Learning (SEL) on the cognitive and emotional development of adolescents. The primary focus is to examine how SEL implementation in educational settings can enhance students' critical thinking, problem-solving skills, and emotional regulation. Using a literature review methodology, this research synthesizes findings from peer-reviewed journal articles, books, research reports, and other relevant publications. The results reveal that SEL significantly improves students' cognitive abilities, including academic performance and collaboration skills, and promotes emotional regulation, fostering healthier social relationships. Furthermore, the study identifies key challenges in SEL implementation, such as inadequate teacher training, limited school resources, and insufficient parental involvement. In conclusion, while various obstacles hinder the successful implementation of SEL, the program has been proven effective in supporting the holistic development of students—both cognitively and emotionally. Addressing these challenges through targeted training and collaborative support from all stakeholders is crucial for maximizing SEL's benefits.